2014
DOI: 10.1371/journal.pone.0106457
|View full text |Cite
|
Sign up to set email alerts
|

Acetate and Bicarbonate Assimilation and Metabolite Formation in Chlamydomonas reinhardtii: A 13C-NMR Study

Abstract: Cellular metabolite analyses by 13C-NMR showed that C. reinhardtii cells assimilate acetate at a faster rate in heterotrophy than in mixotrophy. While heterotrophic cells produced bicarbonate and CO2 aq, mixotrophy cells produced bicarbonate alone as predominant metabolite. Experiments with singly 13C-labelled acetate (13CH3-COOH or CH3-13COOH) supported that both the 13C nuclei give rise to bicarbonate and CO2 aq. The observed metabolite(s) upon further incubation led to the production of starch and triacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…The cia5 mutant, which cannot acclimate to the low CO 2 condition due to the lack of CCM, was grown in the presence of 5% CO 2 . All cultivations were conducted under a photoautotrophic condition in 100 ml Erlenmeyer flask, with 50 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cia5 mutant, which cannot acclimate to the low CO 2 condition due to the lack of CCM, was grown in the presence of 5% CO 2 . All cultivations were conducted under a photoautotrophic condition in 100 ml Erlenmeyer flask, with 50 …”
Section: Methodsmentioning
confidence: 99%
“…8 C. reinhardtii is able to uptake inorganic carbon (HCO 3 À and CO 2 ) and efficiently convert them into organic compounds in the light phase by the means of CCM and photosynthesis. 50 Thus, they can successfully cover their carbon requirement. In the dark phase, however, the light-dependent carbon assimilation process would stop, and the dark respiration starts to increase the internal production of CO 2 .…”
Section: Circadian Rhythm Of Chemotaxis To Hco 3mentioning
confidence: 99%
“…The observation that TAG accumulates during nitrogen deprivation in Chlamydomonas cells cultured heterotrophically in the dark separates the induction of TAG accumulation from photosynthesis. High levels of TAG accumulation have been reported in heterotrophically grown Chlorella species (Miao and Wu, 2004;Liu et al, 2011), and TAG accumulation was also observed in heterotrophically cultured Chlamydomonas after carbon starvation (Singh et al, 2014) and during N deprivation in the presence of high levels (60 mM) of acetate (Fan et al, 2012).…”
mentioning
confidence: 88%
“…Cells were nevertheless exposed to a low light intensity, close to the compensation point, to maintain their photosynthetic metabolism active. Also cells were cultivated in flasks, where CO2 diffusion from the atmosphere is limited in order to further stimulate acetate assimilation from the medium [33]. Three rounds of cultivation in labeled medium were performed in these conditions with a tenfold dilution at every step.…”
Section: Isotope Labeling and Thylakoid Extractionmentioning
confidence: 99%